2012
DOI: 10.2478/s11696-012-0156-0
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid and phytosterol contents of some Romanian wild and cultivated berry pomaces

Abstract: The total oil content and composition of fatty acids and phytosterols of five Transylvanian (Romania) pomaces of wild and cultivated blueberries (Vaccinium myrtillus), wild cowberry (Vaccinium vitis-idaea) and raspberry (Rubus idaeus), and cultivated black chokeberry (Aronia melanocarpa), were determined by capillary gas chromatography. Out of the five pomace oils, the percentages of polyunsaturated fatty acids (PUFAs) ranged from 37 % to 69 %. The lipid classes analysed (PLs — polar lipids, TGs — triacylglyce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 47 publications
3
21
1
1
Order By: Relevance
“…The range of the omega‐6 FA content in the raspberry oil was 53.86 ± 0.47 to 55.83 ± 0.93%, while it was slightly higher in the blackberry seed oil (61.24 ± 0.22 to 63.66 ± 0.49%). These values are in agreement with other reported results to name a few. However, the content of omega‐3 fatty acids was much higher in the raspberry seed oil (29.00 ± 0.20 to 32.97 ± 0.43%) compared to the blackberry seed oil (13.77 ± 0.32 to 14.98 ± 0.64%).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The range of the omega‐6 FA content in the raspberry oil was 53.86 ± 0.47 to 55.83 ± 0.93%, while it was slightly higher in the blackberry seed oil (61.24 ± 0.22 to 63.66 ± 0.49%). These values are in agreement with other reported results to name a few. However, the content of omega‐3 fatty acids was much higher in the raspberry seed oil (29.00 ± 0.20 to 32.97 ± 0.43%) compared to the blackberry seed oil (13.77 ± 0.32 to 14.98 ± 0.64%).…”
Section: Discussionsupporting
confidence: 94%
“…The omega-6 and omega-3 FA contents consequently provided much lower and desirable omega-6 to omega-3 FA acids ratio of 1.69 to 1.86 for the raspberry and 4.25 to 4.45 for the blackberry oil. Similar results were reported in literature [1,15,19,40,45,47]. Correlation coefficients ( Table 6, section b) that considered oleic fatty acid content, omega-6 and omega-3 FA content, as well as their ratio, have shown that blackberry and raspberry oils are very different and only correlated between the treatments of the samples amongst the same oil type.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The oils were extracted from 5 g of seeds, using a methanol/chloroform extraction procedure, according to Yang et al [36] and Dulf et al [46]. The sample was homogenized in 50 mL methanol for 1 min using a homogeniser (MICCRA D-9, Germany), 100 mL chloroform was added, and homogenization was continued for further 2 min.…”
Section: Methodsmentioning
confidence: 99%
“…Steroids are very often hormones and regulators in the body. These compounds are widespread and occur in both animals and plants (Saraiva et al 2011;Dulf et al 2012). Typically, they contain 27 to 30 carbon atoms in the molecule.…”
Section: Introductionmentioning
confidence: 99%